The Association between Specimen Neuromuscular Characteristics and Urinary Incontinence after Robotic-Assisted Radical Prostatectomy - Tomer Bashi; Jonathan Margalioth; Ziv Savin; Ron Marom; Snir Dekalo; Ibrahim Fahoum; Rabab Naamneh; Roy Mano; Ofer Yossepowitch (Diagnostics)
Urinary incontinence after robotic-assisted radical prostatectomy (RARP) has been associated with older age, a longer operative time, a higher BMI, a short membranous urethral length and preoperative erectile function. The authors sought to assess the association between the neuromuscular characteristics and postoperative urinary incontinence. Methods: RARP specimens from 29 men who underwent bilateral nerve sparing were reanalyzed. Urinary incontinence was evaluated using the International Consultation on Incontinence Questionnaire—Short Form (ICIQ-SF) at 6 weeks post surgery and last follow-up. Linear and logistic regression analyses were performed to assess neuromuscular characteristics and incontinence. Results: At the 1-year follow-up, 11 patients (38%) reported severe incontinence (>12 ICIQ-SF score). The median number of peripheral nerves observed at the base and apex in the specimens was 52 (IQR 13–139) and 59 (IQR: 28–129), respectively. Ganglia were present in 19 patients (65%) at the base and 12 patients (41%) at the apex. Additionally, the median proportional area of detrusor smooth muscle fibers at the base was 0.54 (IQR 0.31–1), while the median proportional area of striated muscle fibers at the apex was 0.13 (IQR 0.08–0.24). No statistically significant associations were found. Conclusions: Histologic neuromuscular characteristics were not associated with postoperative urinary incontinence. Enhanced intraoperative evaluation and larger-scale studies may prove useful for the prediction of postprostatectomy incontinence.